THE DEATH KNELL OF ENVIRONMENTAL TOBACCO SMOKE AT PUBLIC SPACES: CONSTITUTIONALITY OF SMOKING RESTRICTIONS AND SMOKE-FREE ZONE LAWS IN MALAYSIA (UUM Journal of Legal Studies, 2021)
Control of tobacco faces a huge obstacle because it is where important health issue has to face the powerful opposition from the wealth influence of tobacco industries (TI). Death and disease caused by tobacco use now constitute a pandemic. Unfortunately, the power and impact of tobacco’s nature and commerce of its addiction make tobacco control a contentious issue of public health. The task of curbing the tobacco pandemic becomes more challenging with the use of human rights arguments and constitutional issues by smokers and the TI. This is a qualitative research on medical and legal aspects of tobacco use and smoking. This paper examines the origin of tobacco and its use as well as the development of scientific and medicalreports relating to the effect of tobacco use particularly smoking. It also demonstrates how national and global policies relating to tobacco were formulated based on the scientific findings and medical reports by giving priority to public health. This is also a legal research relating to international legal framework of tobacco control, namely the WHO Framework Convention on Tobacco Control (WHO FCTC), and the legal regulations relating to tobacco control in Malaysia as well as its enforcement strategies. The legal challenge mounted against the law and policy restricting tobacco use is also examined. The study shows the implementation of WHO FCTC is crucial in fighting tobacco pandemic. The convention also upheld the right of the people to breathe fresh and clean air by prohibiting environmental tobacco smoke (ETS) exposure in public spaces. Thus, the right must be respected by smokers and must not be infringed upon. The decision of the court is lauded because the law and policy relating to tobacco control are in line with rights guaranteed by the Federal Constitution and in tandem with WHO FCTC of which Malaysia is a party.